Traditional house of Negeri Sembilan: interior layout plan and relation to compatibility Islamic principles and matrilineal / Setiawan Hardono … [et al.] - Hardono, Setiawan; Bahauddin, Azizi; Abdullah, Aldrin; Maliki, Nor Zarifah (Division of Research and Industry Linkages, UiTM Melaka, 2014)
This article studies the Islamic element in the layout of the interior of a traditional house of Negeri Sembilan and its relationship to the concept of custom mother or matrilineal kinship system. The uniqueness ofthe design and layout ofthe interior of a traditional Negeri Sembilan house is often associated with Adat Perpatih. Moreover Islam is one of the cultural elements associated with the unique characteristics of its architecture. Both Islam and matrilineal elements have a harmonious compatibility in particular in shaping the interior layout of the traditional houses. Therefore, the objective of this study was to identify and analyze the relationship compatibility of Islam in the matrilineal elements associated with this item. The unique design has a strong correlation with the five (5) main characters involving the organization of interior space house ‘privacy,security,social, health and dignity. Studies such as this should be done in order to provide exposure and understanding to the public, so that the uniqueness of the architecture and functionality of a traditional Negeri Sembilan house can continue to be preserved. This study uses a methodology review, analysis of previous studies and ethnographic methods. Data collection was acquired through a process of observation, interviewing, and hiring -related photos in several locations of the study. The methodology of this study was to produce a realistic study to confirm the compatibility of Islam in matrilineal element in designing the layout of the interior o f a traditional house of Negeri Sembilan.